Heart failure and iron deficiency anemia in Italy: results from CARMES-1 registry. (May 2013) - Caira, Carmen; Ansalone, Gerardo; Mancone, Massimo; Canali, Emanuele; Pagliaro, Michela; Fratarcangeli, Lara; Aznaran, Carlos Alberto Centurion; Gatto, Maria Chiara; Pietro, Riccardo Di; Fedele, Francesco
Aims: To assess the prevalence of anemia and iron deficiency anemia in heart failure (HF) patients, to evaluate the effectiveness of current iron deficiency treatment strategies after discharge, and to analyze hospital readmissions and mortality rates in patients with and without anemia.Patients & methods: A patient registry-based, multicenter, retrospective, observational, cohort study of 418 hospitalized HF patients in Italy, monitored from 1 March 2010 to 30 March 2011.Results: Among patients with HF, 35.9% had anemia at admission; only 51.3% were treated with current iron deficiency treatment strategies during hospitalization and then only 29% of patients who were anemic at discharge were treated with iron at home. After a 4-week follow-up, only 11% of these patients reached the hemoglobin target value (study primary end point). However, current iron deficiency treatment strategies were not significantly associated with reduced risk of rehospitalization, but with a significantly reduced mortality rate after a 6-month follow-up (study secondary end points: 11.7 vs 51.7%; p < 0.0001).Conclusion: In HF patients, there is poor attention paid to anemia, its causes and treatment. Current iron deficiency treatment strategies are mismanaged and CARMES-1 demonstrated that they appear to be insufficient at improving patient outcome in terms of rehospitalization rate reduction, generating high costs, which could be avoided through an optimized treatment strategy. Therefore, more efficacious, efficient and cost–effective treatment strategies are required in Italy for HF patients with iron deficiency anemia to meet this unmet medical need.